Prevalence of Chronic Kidney Disease among Patients Attending a Specialist Diabetes Clinic in Jamaica - Ferguson, TS (West Indian Med J, 2015)
OBJECTIVES: To estimate the prevalence of chronic kidney disease (CKD) among patients attending the University Hospital of the West Indies (UHWI) Diabetes Clinic and to determine the proportion of patients at high risk for adverse outcomes. METHODS: We conducted a cross-sectional study among patients attending the UHWI Diabetes Clinic between 2009 and 2010. Trained nurses administered a questionnaire, reviewed dockets, and performed urinalyses. Estimated glomerular filtration rate (eGFR) was calculated using the Chronic Kidney Disease Epidemiology Collaboration (CKD-EPI) equation. Albuminuria was assessed using urine test strips for protein and microalbumin. Chronic kidney disease was defined as an eGFR < 60 ml/min/1.73m(2) or albuminuria ≥ 30 mg/g creatinine. Risk of adverse outcome (all-cause mortality, cardiovascular disease and kidney failure) was determined using the Kidney Disease: Improving Global Outcome (KDIGO) 2012 prognosis grid. RESULTS: Participants included 100 women and 32 men (mean age, 55.4 ± 12.9 years, mean duration of diabetes, 16.7 ± 11.7 years). Twenty-two per cent of participants had eGFR < 60 ml/min/1.73m(2). Moderate albuminuria (30–300 mg/g) was present in 20.5% of participants and severe albuminuria (> 300 mg/g) in 62.1%. Overall prevalence of CKD was 86.3% (95% CI 80.4%, 92.2%). Based on KDIGO risk categories, 50.8% were at high risk and 17.4% at very high risk of adverse outcomes. CONCLUSION: Most patients at the UHWI Diabetes Clinic had CKD and were at high or very high risk of adverse outcomes. Further studies to determine the burden of CKD in other clinical settings and to identify the best strategies for preventing adverse outcomes in developing countries need to be conducted.